Mind the Gap: The Effects of Temporal and Spatial Separation in Localization of Dual Touches on the Hand - Sadibolova, Renata; Tamè, Luigi; Walsh, Eamonn; Longo, Matthew R. (Frontiers in Human Neuroscience, 2018)
In this study, we aimed to relate the findings from two predominantly separate streams of literature, one reporting on the localization of single touches on the skin, and the other on the distance perception of dual touches. Participants were touched with two points, delivered either simultaneously or separated by a short delay to various locations on their left hand dorsum. They then indicated on a size-matched hand silhouette the perceived locations of tactile stimuli. We quantified the deviations between the actual stimulus grid and the corresponding perceptual map which was constructed from the perceived tactile locations, and we calculated the precision of tactile localization (i.e., the variability across localization attempts). The evidence showed that the dual touches, akin to single touch stimulations, were mislocalized distally and that their variable localization error was reduced near joints, particularly near knuckles. However, contrary to single-touch localization literature, we observed for the dual touches to be mislocalized towards the ulnar side of the hand, particularly when they were presented sequentially. Further, the touches presented in a sequential order were slightly “repelled” from each other and their perceived distance increased, while the simultaneous tactile pairs were localized closer to each other and their distance was compressed. Whereas the sequential touches may have been localized with reference to the body, the compression of tactile perceptual space for simultaneous touches was related in the previous literature to signal summation and inhibition and the low-level factors, including the innervation density and properties of receptive fields (RFs) of somatosensory neurons.